Developing Adaptable Clinical Practice Guidelines for Remote and Telehealth Environments - Denalt Rands; Alexy Revi (Yayasan Adra Karima Hubbi, 2025)
Background: The rise of digital communication has led to the widespread use of emojis, transforming them into a new form of language. Emojis are not only visual representations but also convey emotions, context, and nuances that words alone may not fully express. Understanding the evolution of emoji language is crucial for comprehending its impact on communication and social interactions. Objective: This study aims to explore the linguistic and social implications of emoji usage in digital communication. The research focuses on how emojis influence language, affect interpersonal interactions, and contribute to the development of digital communication norms. Methods: A mixed-methods approach was employed, combining quantitative analysis of emoji usage patterns with qualitative interviews. The quantitative analysis involved examining large datasets of text messages and social media posts to identify trends and patterns in emoji usage. Qualitative interviews were conducted with diverse participants to gain insights into their perceptions and experiences with emojis in communication. Results: The findings indicate that emojis serve multiple functions in digital communication, including emotional expression, tone modulation, and contextual clarification. Emojis were found to enhance the expressiveness of messages, reduce misunderstandings, and create a sense of closeness between communicators. The study also revealed variations in emoji usage based on age, gender, and cultural background, highlighting the role of emojis in reflecting social identity and group dynamics. Conclusion: Emojis have evolved into a significant component of digital communication, influencing both linguistic practices and social interactions. Their ability to convey emotions and context makes them a powerful tool for enhancing communication in digital spaces. Understanding the implications of emoji usage can inform the development of more effective communication strategies and digital platforms.